2009
DOI: 10.1021/jp9030333
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Dynamics of Laterally Frozen Nanoparticles Specifically Attached to Biomembranes

Abstract: The strongly polarized light scattering of gold nanorods at their longitudinal plasmon frequency allows for the tracking of single gold nanorod lateral positions and orientations via optical dark-field microscopy. We monitor both lateral and rotational diffusion of polymer-coated gold nanorods attached to artificial biomembranes on solid supports. The attachment is mediated by the biotin-streptavidin receptor−ligand system, but weak interaction is also observed in the absence of streptavidin. In the latter cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…The rotational velocity of these nanorods was found to be even slower than that of the nanorod confined on the lipid bilayer through limited number of biotin/streptavidin interactions on the side wall (∼0.025 s −1 ). 23 These interesting results imply that the hypothesis of spatial confinement effect through the formation of lipid pores on the lipid membrane is not sufficient to cause the simultaneously confined lateral and rotational motions for the nanorod.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The rotational velocity of these nanorods was found to be even slower than that of the nanorod confined on the lipid bilayer through limited number of biotin/streptavidin interactions on the side wall (∼0.025 s −1 ). 23 These interesting results imply that the hypothesis of spatial confinement effect through the formation of lipid pores on the lipid membrane is not sufficient to cause the simultaneously confined lateral and rotational motions for the nanorod.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By fitting the power spectral density of the intensity traces with the Lorentzian function ( Supplementary Fig. S5) 44 , we found that the rotation characteristic time of the in-plane rotation at the pauses (8.7-14.3 ms) is longer than that of the random Brownian motion (2.1 ± 0.3 ms), indicating the rotation at these long pauses is slower than the Brownian motion.…”
Section: Rotation Of Endocytic Vesicles Reported By Gold Nanorodsmentioning
confidence: 99%
“…More recently, their plasmon resonance has been employed for more elaborate optical nanoscopicsensing schemes. The plasmon resonance of coupled particles depends on interparticle distance [1][2][3][4], and the strong plasmonic light scattering efficiency allows for the visualization of single nanorods, for example for orientation sensing [5][6][7][8]. Furthermore, the resonance position is influenced by the particle charge [9,10] and the refractive index of the particle's immediate environment [11].…”
Section: Introductionmentioning
confidence: 99%